Goal Model to Business Process Model: A Methodology for Enterprise Government Tourism System Development - Ahmad Nurul Fajar; Imam Marzuki Shofi (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The critcal factor in successfully in system development is the requirement phase. The requirement should meets with its purpose. In order to achieve it, the methodology for requrement analysis is needed. Nowdays, the complexity of e-governemnt applications is grown significantly in the government environment. E-government applications should be developed based on regulations in order to achieve the goal model of government entitties. However, the goal model could not used directly to make business process model. In order to solve this problem,this paper presents and proposed a Methodology to extract goal model into business process model that called GBPM Methodology. It can support the requirement analysis phase, especially in enterprise government tourism system. This methodology consists of two methods, there are (1) Method for convert goal model to business use case diagram, (2) Method for convert business use case diagram to activity diagram. We do the experiment in e-government applications domain. This methodology suitable with enterprise government tourism system development.